METHODOLOGICAL RECOMMENDATIONS FOR SOLVING NON-STANDARD EQUATIONS - Karimova Nargiza Mamurkhanovna (Modern American Journals, 2025)
This article provides a brief analysis of the literature on the topical problem of solving non-standard equations, provides guidelines for teaching schoolchildren to solve non-standard equations and organizing the search for such a solution. In the course of the study and the experience of working with schoolchildren at the seminar "preparing for the exam" for teachers and students in grades 10-11, it was revealed that the greatest difficulty is the search for solutions to non-standard equations containing several functions. According to the author, the use of standard methods does not always allow solving equations of this type. However, the problem of teaching the search for solutions to non-standard equations in the scientific, methodological and educational literature is not sufficiently developed. Numerous problem books contain various examples of solving non-standard equations without their detailed analysis and methodological recommendations for organizing the search for their solution. The author proposes methodological recommendations for teaching students to find solutions to non-standard equations using a system of leading questions and some non-standard methods for their solution, in particular, the assessment method, analytical-functional method and the use of homogeneity.
Keywords: Equation solution, estimation method, domain of definition, domain of values, solution methods.